Topological surface states and superconductivity in non-centrosymmetric PbTaSe2. (12th May 2021) - Guan, Syu-You; Chen, Peng-Jen; Chuang, Tien-Ming
Abstract: A topological superconductor exhibits chiral p -wave pairing symmetry and hosts Majorana fermions. The predicted emergent phenomena in such a system and its application for topological quantum computation make it a pivotal focus of research. Stoichiometric non-centrosymmetric superconductor PbTaSe2 has emerged as a strong candidate material due to possible parity mixing in bulk superconductivity and superconducting topological surface state (TSS). In this review, we summarize recent progress on the study of PbTaSe2, including bulk superconductivity, topological band structure, superconducting TSS and the elusive Majorana bound state within.